SISTEM PENGAWASAN TERHADAP HAKIM KONSTITUSI DALAM MEWUJUDKAN INDEPENDENSI HAKIM - Eza Aulia (Jurnal Public Policy, 2016)
The main problem in this study is whether the system of internal supervision within the Court can realize the independence of judges and whether the constitutional Judge MK can be monitored externally. Constitutional Court Regulation No. 2 Year 2014 About the Honorary Council of the Constitutional Court can not guarantee the realization of the independence of the Constitutional Court, it can be seen from the supervisory role of the Board of Ethics that ispassively waiting for reports from the public in the event of violations committed by the Constitutional Court, then the authority and composition both the membership of the Board of Ethics and the Court of Honor Assembly that require improvement, so ensuring the neutrality and mutual balance between the elements contained in the Board of Ethics and the Council of Honor Court. It is recommended that the Court made improvements with respect to the internal control system by means of amending the Constitutional Court Regulation No. 2 of 2014. It should be carried out a review of the elements of the membership of the Board of Ethics and Honor Council and the authority of the institution so that it can more leverage in carrying out its functions, that the surveillance system is applied can be realized a guarantee for the independence of the Constitutional Court. Keywords: Monitoring System, Constitutional Justice, Independence of Judges, Constitutional Court